A mediação pedagógica na escrita inventada com crianças de cinco anos - Paula Moreira Martins de Oliveira Lanza (2018)
Invented writing is an action that generates transformations in the childs thinking insofar as it draws attention to the sound patterns of words and the way in which they can be recorded. The mediation of the adult when the child performs the invented writing of words, that is, when he/she produces graphical representations for oral words, using known letters, potentiates the effects of this action in the development and learning of the children. The aim of the present investigation is to characterize and analyze pedagogical mediation strategies in the writtenproductions of five-year-old children, which may favor the process of metalinguistic reflection implied in the initial learning of the written language. The Invented Writing Program was developed based on situations of collaborative word-writing production, in which children aremobilized to explain, argue, describe their ideas about the alphabetical writing system to reach a consensus on how to write certain words. For this investigation, the perspective of intervention research with a qualitative analysis of the interaction processes that occurredduring the intervention program in the invented writing of the children was adopted. It was established a dialogue with Alves Martins (1994), Alves Martins and Silva (1999), Ferreiro and Teberosky (1985), Morais (2004, 2012), Monteiro (2013, 2014a, 2014b), Soares (2016) and Vygotsky (1989, 2007), in order to reflect on the process of acquisition of the alphabetical writing system. The analysis of the interactions that took place in the working group with the children allowed to identify ten categories of interventions, which are characterized from specific functions with the elaboration of the children. The analysis of childrens behaviors throughout the group meetings and their written productions in the initial and final evaluations suggest that the Invented Writing Program may have had a strong influence on conceptualization process of the children